Self-admitted behavior and perceived use of performance-enhancing vs psychoactive drugs among competitive athletes - Uvacsek, M.; Nepusz, T.; Naughton, D. P.; Mazanov, J.; Ranky, M. Z.; Petroczi, A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The relationships between projected use, self-reported behavior and attitudes to performance-enhancing (PED) and recreational (RD) drugs were investigated among 82 competitive Hungarian athletes, with 14.6% admitting using PED and 31.7% using RD. Both the observed doping estimations (even those made by non-users) and self-admitted use were considerably higher than the average rate of positive doping tests (2% of all tests). The notable overestimation by PED users (34.6% vs 16.9%) was in keeping with the false consensus effect. A prediction model with attitude and projection to the likelihood of PED use suggested at least a 70% chance of self-involvement of athletes, with responses at or above the median scores (Performance Enhancement Attitude Scale >/= 60 and estimation >/= 50%) on the two independent measures. Users overestimated the prevalence of doping in their sport (P=0.007) but not RD use, with the converse holding for RD users' views of doping (P=0.029). PED users also showed a significantly more lenient attitude toward doping (P<0.001). This domain-specific characteristic adds new information to the ongoing research effort in understanding drug-doping co-morbidity. The reasons for elevated in-group projection are discussed, along with the potential application of this phenomenon in doping epidemiology studies.